2017
DOI: 10.1371/journal.pone.0173833
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and enhanced detection of tumor invasion of peritoneal membranes

Abstract: Tumor invasion of the peritoneal membrane may have an adverse prognostic significance, but its histopathologic features can be diagnostically difficult to recognize. We observed that local peritoneal injury associated with tumor invasion is characterized by activation and proliferation of serosal stromal cells that express cytokeratin, a characteristic property of injured serosal membranes that may have diagnostic utility. To explore this, we examined 120 primary tumors of the gastrointestinal tract and pancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…For these molecules, the immunostaining was less intense than that observed for cytokeratins and calretinin. Similar expression of mesothelial markers by subserosal fibroblasts, including CAFs, has been reported in a few other studies where pathologists are adviced not to confuse cytokeratin-positive fibroblasts for neoplastic cells [27][28][29]. In addition to cytokeratins, Chen J.H.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…For these molecules, the immunostaining was less intense than that observed for cytokeratins and calretinin. Similar expression of mesothelial markers by subserosal fibroblasts, including CAFs, has been reported in a few other studies where pathologists are adviced not to confuse cytokeratin-positive fibroblasts for neoplastic cells [27][28][29]. In addition to cytokeratins, Chen J.H.…”
Section: Discussionsupporting
confidence: 69%
“…In addition to cytokeratins, Chen J.H. and Borges M. [29] describe the subserosal expression of other mesothelial markers as well. For these authors, such expression is evident, but it is not interpreted as a MMT process.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our data revealed that more adequate pathologic criteria of pT4a is further required. Recently, utility of CK7 which highlight mesothelial cells was reported to be useful to detect pT4a in colon cancer, and further investigation would be required 31 . As for 2 inconsistent negative data as a prognostic factor of ELI, one performed elastic stain only in 47 of 290 cases, and another adopted special elastic stain.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, utility of CK7 which highlight mesothelial cells was reported to be useful to detect pT4a in colon cancer, and further investigation would be required. 31 As for 2 inconsistent negative data as a prognostic factor of ELI, one performed elastic stain only in 47 of 290 cases, and another adopted special elastic stain. Routine use of elastic stain, and EVG or modified resorcine-fuchsin method for elastic stain is strongly recommended.…”
Section: Discussionmentioning
confidence: 99%